Multimodal interface and reliability displays: Effect on attention, mode awareness, and trust in partially automated vehicles - Monsaingeon, Noé; Caroux, Loïc; Langlois, Sabine; Lemercier, Céline (Frontiers in Psychology, 2023)
The goal of this study is to evaluate the effect of a multimodal interface indicating the limits of automation to stimulate appropriate level of attention, induce accurate mode awareness and trust in automation in Level-2 vehicles. Participants drove in a driving simulator with partially automated systems and were confronted with surprising situations of suspension of automated systems in different contexts. They drove the simulator during three driving sessions, with either a multimodal interface indicating limits of automation or a visual basic interface. Their driving performance, ocular behaviour, subjective evaluation of trust and workload were evaluated. The results revealed that the multimodal interface stimulates appropriate level attention, increases mode awareness and trust in automation, but that these effects are context dependent. The indications of the limits of automation improved the knowledge regarding automation but this knowledge did not necessarily lead to improved driving performance. Design solutions are discussed to support improvement of driving performance for take-overs in Level-2 vehicles.